Gastrointestinal parasites and ectoparasites of Bradypus variegatus and Choloepus hoffmanni sloths in captivity from Costa Rica - Sibaja-Morales, Karen D. (2009)
Sloths may serve as host to a wide range of parasites. However, there is little information available on the types of parasites that affect Costa Rica's sloth population. During a 1-yr period, 65 specimens of Costa Rican sloth species (Choloepus hoffmanni; n = 56) and Bradypus variegates; n = 9) from a local zoo were sampled. Fecal samples were evaluated using two different diagnostic techniques, Sheather's flotation and sedimentation. Concurrently, these sloths were examined for ectoparasites. Gastrointestinal parasites were found in 14 sloths (21.5%), from which 13 animals were C. hofffmanni and one was B. variegatus. Gastrointestinal parasites were recognized as Coccidia 71.4% (10/14), Cestoda 21.4% (3/14), and Spiruroidea 7.1% (1/14). Coccidia and cestodes were seen in C. hoffinanni, and spirurids were identified in B. variegatus. Among 27 sloths examined, only six had dermal problems (five C. hoffmanni and two B. variegatus). Ectoparasites recovered were Sarcoptes scabiei (Acari, Sarcoptidae) mites and Amblyomma varium (Acari, Ixodidae) ticks. This is the first time that cestode strobilae and nematode eggs are reported in sloth feces and that Monezia benedeni and L. leptocephalus were found in captive sloths.